Agroforest woody residual biomass-to-energy supply chain analysis: Feasible and sustainable renewable resource exploitation for an alternative to fossil fuels - Nunes, Leonel J.R.; Casau, Margarida; Dias, Marta Ferreira; Matias, J.C.O.; Teixeira, Leonor C. (Results in engineering, 2023)
Agroforest woody residual biomass can play an essential role in the decarbonization of energy production and in meeting the targets imposed for carbon neutrality. However, due to the constraints caused by some intrinsic characteristics, such as its low density, low calorific value, high heterogeneity and territorial dispersion, its management hampers in the collection and transport processes for recovery. In this article, the supply chain associated with the energy recovery of agroforestry woody residual biomass is analyzed to clarify the positive and negative points affecting the viability and feasibility of energy recovery projects. For this purpose, a PEST and a SWOT analysis were carried out. It was identified that the main constraints are related with the economic aspects, which are directly depending on the optimization of the entire supply chain, from the cutting operations, passing through the intermediate tasks (which may or may not add value), and transport to the final destination for energy recovery. •Biomass as an energy option is discussed.•Biomass to energy supply chain is analyzed.•PEST and SWOT analysis are presented:•Biomass to energy supply chain bottle necks are identified and discussed.